PRESIDENTIAL SYMPOSIUM: FUNCTIONAL ABILITY IN LATE LIFE—IMPLICATIONS FOR RISK FACTOR PREVENTION AND HEALTH CARE UTILIZATION. (11th November 2018) - Strotmeyer, E S; Ensrud, K
Abstract: Functional ability and disability-free survival are optimal goals for individuals and clinical care in late life. Therefore, an appreciation of factors contributing to functional ability at the oldest ages is critical for shaping preventive care and health care services. The Health Sciences Presidential Symposium will describe patient characteristics that are predictors of hospitalization readmission, health care costs and disability-free survival in late life. Additionally, the speakers will highlight novel methodology for linking characteristics in late life populations with functional endpoints in epidemiologic and health care datasets. The prediction of functional ability at the oldest ages will be described, including: 1) longitudinal risk factor trajectories predicting survival to age 90 years, free of cardiovascular disease, cognitive impairment and disability (Odden); and 2) a validation of claims-based frailty index from measured physical performance and clinical outcomes (Kim). Health care utilization factors will be characterized as: 1) socioeconomic, disability and multimorbidity factors impacting high hospital readmission rates (Roberts); and 2) depressive symptoms, functional limitations, and multimorbidity factors contributing to total health care costs (Schousboe). The Discussant (Ensrud) will provide an overview of the opportunities and challenges of for assessing disability in late life, with a focus on use of large epidemiologic datasets and administrative claims. An understanding of key characteristics predicting functional ability at the oldest ages has implications for risk factor prevention and health care utilization.